Monetary and macroprudential policies with direct and indirect financing: Implications for macroeconomic stability - Jan Bruch; Franz Seitz; Uwe Vollmer (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2024)
We assess the impact of macroprudential measures on macroeconomic stability using a DSGE model in which firms can access both direct and indirect financing. The model is calibrated with data from the euro area. We compare two different macroprudential rules (time-invariant and counter-cyclical) in the presence of a monetary policy shock and a macroprudential policy shock. We find that the macroprudential rule has little impact on the adjustment dynamics to a monetary and macroprudential shock. Direct financing increases the impact of monetary shocks on the volatility of financial variables but not on output and inflation. Simultaneous monetary policy and macroprudential policy shocks do not alter the reaction of inflation compared to a monetary policy shock but cause permanent output losses. – – Wir untersuchen die Auswirkungen makroprudenzieller Maßnahmen auf die makroökonomische Stabilität mit Hilfe eines DSGE-Modells, in dem Unternehmen sowohl Zugang zu direkter als auch zu indirekter Finanzierung haben. Das Modell wird mit Daten des Euroraums kalibriert. Wir vergleichen zwei verschiedene makroprudenzielle Regeln (zeitinvariant und antizyklisch) in Gegenwart eines geldpolitischen Schocks und eines makroprudenziellen Schocks. Wir stellen fest, dass die makroprudenzielle Regel kaum Auswirkungen auf die Anpassungsdynamik bei einem geldpolitischen und makroprudenziellen Schock hat. Die direkte Finanzierung erhöht die Auswirkungen von monetären Schocks auf die Volatilität der Finanzvariablen, nicht aber der Produktion und Inflation. Gleichzeitige geldpolitische und makroprudenzielle Schocks verändern die Reaktion der Inflation im Vergleich zu einem geldpolitischen Schock nicht, verursachen aber dauerhafte Produktionsverluste.
Keywords: E12; E31; E32; E58; 330; Monetary Policy; Macruprudential Policy; Inflation; Business Cycle; DSGE